Analisis Kinerja Keuangan Pemerintah Daerah Kabupaten Tapanuli Tengah - Heri Faisal Harahap (Universitas Batanghari Jambi, 2020)
This research was aimed to know the financial performance of the Central Tapanuli regency government in 2016-2018. This research is quantitative descriptive. The research used secondary data in form of Financial Report of Central Tapanuli regency in 2016-2018. The analysis technique in this study calculates and analyzes the ratio of the decentralization level, regional financial dependence and effectiveness. The results of this study indicate that the financial performance of the Central Tapanuli Tengah Regional Government is generally said to be quite good, although the degree ratio is still relatively low, financial dependence on the Central / Provincial Government is still very high and the receipt of Regional Original Revenue does not reach the budgeted target. Central Tapanuli Regency Government to update the data of regional taxpayers, explore the potential of new sources of local revenue, and increase the socialization of tax benefits and user fees.